Views of Chiang Mai: The contributions of remote-sensing to urban governance and sustainability - Louis Lebel (2018)
From space, the rice fields of the Mae Nam Ping basin around Chiang Mai curve like a fetus around the square heart of the old city, nourished by a placenta of forested hills (Plate 10.1). If we zoom in closer to the heart, the square moat, road and ramparts of the old city (Plate 10.2), we can make out the arterial roads streaming out from ancient city gates to feed the growing body marked by the curves of new ring roads (Plate 10.2). The lowland rice farmer's view is of a society nurtured by, but separate from, wild nature, with the river, Mae Nam, literally the mother. © 2007 Springer-Verlag Berlin Heidelberg.